2015
DOI: 10.1186/s12906-015-0524-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the anti-diabetic potential of Australian Aboriginal and Indian Ayurvedic plant extracts using cell-based assays

Abstract: BackgroundPlant-derived compounds have been used clinically to treat type 2 diabetes for many years as they also exert additional beneficial effects on various other disorders. The aim of the present study was to investigate the possible mechanism of anti-diabetic activity of twelve (seven Australian Aboriginal and five Indian Ayurvedic) plant extracts.MethodsThe ethanolic plant extracts were investigated for glucose uptake and adipogenesis in murine 3T3-L1 adipocytes. Cytotoxicity studies were also carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…However, only a limited number of species have been extensively studied. There has been limited previous research on Australian Aboriginal medicinal plants for activity against enzymes relevant to carbohydrate metabolism [21, 37] and to our knowledge, no previous studies on Australian medicinal plants for antiglycation activities and inhibition of ACE. Our research is a collaboration between Aboriginal and University-based researchers with research into the efficacy and safety of their traditional plant medicines driven and guided by Traditional Owners.…”
Section: Resultsmentioning
confidence: 99%
“…However, only a limited number of species have been extensively studied. There has been limited previous research on Australian Aboriginal medicinal plants for activity against enzymes relevant to carbohydrate metabolism [21, 37] and to our knowledge, no previous studies on Australian medicinal plants for antiglycation activities and inhibition of ACE. Our research is a collaboration between Aboriginal and University-based researchers with research into the efficacy and safety of their traditional plant medicines driven and guided by Traditional Owners.…”
Section: Resultsmentioning
confidence: 99%
“…Among the five fractions obtained, F5 gave the lowest IC 50 value. Even though the value was higher than the NCI reference value, plant extracts with IC 50 values within range of 30 to 200μg/ml have the potential to be refined into anticancer agents [19,22] Based on the overall evaluations of antiproliferative activities among PFME and its fractions, the IC 50 value of F5 was higher than the PFME. The findings suggested that the PFME was more potent than the fractions.…”
Section: Antiproliferative Studies Of Pfme and Fractions On Selected mentioning
confidence: 99%
“…On the other hand, preadipocytes were also maintained with fresh FBS-DMEM for the entire induction period. At the end of the induction period oil red O staining assay [35] was performed to monitor the degree of differentiation. For the comparison of triglyceride accumulation photo microscopic assessment was also carried out.…”
Section: Percent Viability = (Od Of Untreated Cells -Od Of Treated Cementioning
confidence: 99%